Photography and modernization of the press in Brazilian capital: the first fifty years of the 20th Century - Louzada, Silvana (Brazilian journalism research, 2009)
The process which created the conditions for the development of mass media press in Brazil was consolidated in the first half of the 20th Century with the emergence of newspaper companies based on an industrial form of production, the modernization of the writing style and design, plus the use of photography as a newsy element. There was a strong investment in technology in order to modernize the nation and photography, as a technical image par excellence, started to portray the acceleration of the passage of time that was accentuated by the 1890’s. In the beginning of the 20th century a new technological trend occurred mediated by the photographic apparatus and diffused through the newspaper and illustrated magazines pages that were multiplying in the nation’s capital, Rio de Janeiro. The press used photography and a series of technological artifacts to acquire the status of a modern entity and multiply the number of readers, changing its forms of production and its auto-referential discourse, starting to be more and more the icon of modernity. The technologies capable of giving a wider dimension to the concept of time and space were decisive in shaping the new symbolic world which emerged since the turn of the century. The world got closer and more visible, the perception of the “other” changed gradually and temporality took on a new dimension. This article traces a panorama of the use of photography by the main newspapers published in the capital of Brazil in the first half of the 20th century, seeking in photography the reflection of the modernizing process that Brazilian society desired and underwent.